Analysis of spatial distribution of bacterial community associated with accumulation of volatile compounds in Jiupei during the brewing of special-flavor liquor. (August 2020) - Li, Kaimin; Chen, Yanru; Liu, Ting; Deng, Mengfei; Xu, Ziwen; Fu, Guiming; Wan, Yin; Chen, Feng; Zheng, Fuping
Abstract: Jiupei (JP) of a Chinese special-flavor liquor was investigated in regards of its dynamic changes of bacterial community, the accumulation of volatile compounds, and physicochemical parameters in terms of pH, moisture content, total acidity, contents of reducing sugars and amino nitrogen. The results indicated that Lactobacillales and Bacillales were the predominant bacterial communities in the JP, and there was no significant difference (P > 0.05) in bacterial communities between the surface JP (SJP) and under JP (UJP). Acids, alcohols and esters had large contents compared with other volatile compounds in the JP. Among them, the esters had the highest content, while the acids showed the lowest content. In addition, it was found that Lactobacillus genus were the key factor responsible for the accumulation of esters compounds, and there were close correlations between the Lactobacillus genus, and contents of acids and alcohols. These results have provided a basis for the further research on the accumulation mechanism of volatile compounds in the brewing process of special-flavor liquor. Highlights: Lactobacillales and Bacillales were predominant bacterial communities in Jiupei. No significant difference in bacterial communities between the SJP and UJP. Lactobacillus genus was key factor responsible for the accumulation of esters.